2007
DOI: 10.1111/j.1445-2197.2007.04210.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Management of Acute, Traumatic Compartment Syndrome of the Leg in Australia

Abstract: There is variation in the management of acute, traumatic compartment syndrome of the leg in Australia. The development of evidence-based clinical practice guidelines may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Its prompt diagnosis is mostly based on clinical criteria (69), although direct compartment pressure measurements have been used in certain clinical scenarios to confirm a suspected diagnosis (7). Once the diagnosis of an extremity compartment syndrome (ECS) is made treatment entails decompressive fasciotomy (7,8,10).…”
Section: Introductionmentioning
confidence: 99%
“…Its prompt diagnosis is mostly based on clinical criteria (69), although direct compartment pressure measurements have been used in certain clinical scenarios to confirm a suspected diagnosis (7). Once the diagnosis of an extremity compartment syndrome (ECS) is made treatment entails decompressive fasciotomy (7,8,10).…”
Section: Introductionmentioning
confidence: 99%
“…A review from Canada over a 10-year period reported that 77% of plaintiffs had permanent disability and 55% of cases had a judgement for the plaintiff or an unfavourable decision for the physician, with the primary clinical issue a delay or failure to diagnose ACS [92]. Despite all this evidence highlighting the issues with a delay in the diagnosis, there remains an extraordinary lack of consistency in the clinical assessment of the condition [93,94].…”
Section: Limitations and Pitfallsmentioning
confidence: 99%
“…Despite the frequency with which ALCS occurs, and its associated morbidity, there are currently no management guidelines available for the condition. A recent survey revealed variation in the management of ALCS in Australia 4 …”
Section: Introductionmentioning
confidence: 99%